Microtremor Microzonation Based on Seismic Vulnerability Index (Kg) Using HVSR (Horizontal To Vertical Spectral Ratio) Method in Kapanewon Berbah, Sleman, D.I.Yogyakarta: Mikrozonasi Mikrotremor Berdasarkan Indeks Kerentanan Seismik (Kg) Menggunakan Metode HVSR (Horizontal To Vertical Spectral Ratio) di Kapanewon Berbah, Sleman, D.I.Yogyakarta - Maryani, Tri (Sunan Kalijaga Journal of Physics, 2024)
The 2006 Bantul Earthquake centered on the Opak River Fault has caused many casualties and damage to buildings, including in Kapanewon Berbah, Sleman. Kapanewon Berbah is the most affected area in Sleman Regency, because it is located in the red zone near the Opak Fault line. This study uses the HVSR (Horizontal to Vertical Spectral Ratio) method which aims to determine the soil conditions in Kapanewon Berbah based on the dominant frequency and dominant period microzonation, as well as to determine the level of damage based on the dominant amplification value and the seismic vulnerability index. The microtremor data measured at 17 points are processed in geopsy software so that the dominant frequency and amplification values are obtained. Furthermore, the calculation is carried out on Microsoft Excel in order to obtain the value of the dominant period and the seismic vulnerability index. The dominant period is inversely proportional to the dominant frequency value, while the seismic vulnerability index value is obtained from squaring the amplification divided by the dominant frequency. These parameters are processed in surfer12 software in order to obtain a microzonation map based on each parameter. Based on the Kapanewon Berbah microzonation map, a low dominant frequency value is obtained in the range 0.65 - 2.02 hz which shows soft soil conditions in the form of thick sediment; high dominant period values in the range 0.88-1.46 s which indicates very soft soil conditions; high amplification values at the range 4.9-6.1 includes a high level of damage; and the high seismic vulnerability index value is in the range 18.9 to 41.5. The most stable location is at the TA4 measurement point in Tegaltirto Village and the most prone location to experience damage is at the TA2 measurement point in Kalitirto Village.